Psychological capital in increasing perceived organizational support in traffic police members - Fadilah, Amaliah; Hurriyati, Dwi (INSPIRA: Indonesian Journal of Psychological Research, 2023)
Traffic police are responsible for maintaining order and safety on the roads, which involves a series of tasks that are not always easy to perform. Despite this, members of the traffic police remain loyal in carrying out their crucial duties because of the positive psychological conditions that members have, giving rise to positive perceptions of the traffic police in carrying out their duties. This study is intended to determine the relationship between psychological capital and perceived organizational support in police members in the traffic unit. The method used by researchers is quantitative with a sampling technique, namely simple random sampling. One hundred five traffic police members became participants in this study. Data analysis of the results of this study was carried out using a simple regression test, which showed acceptance of the proposed hypothesis. Based on the results of the data analysis, there is a relationship between psychological capital and perceived organizational support for police officers in the traffic unit. These results can be seen from the contribution value between psychological capital and perceived organizational support, which is 53%. This research confirms the importance of one's positive psychological state to increase perceived organizational support.